BS EN IEC 62841-2-3 AMD AA. Electric motor-operated hand-held tools, transportable tools and lawn and garden machinery. Safety. Part 2-3. Particular requirements for hand-held grinders, disc-type polishers and disc-type sanders (9th July 2020) - British Standards Institution,
No abstract available